Assessment of Indoor Air Quality Performance in a Building at Kemaman Terengganu - Razali, Mohd Azahari; Semang, Stewart Sumping; Sani, Winardi; Taweekun, Juntakan (International Journal of Integrated Engineering, 2024)
Violations of IAQ regulations can lead to sick building syndrome (SBS), which manifests as symptoms like respiratory difficulties, eye irritation, skin issues, and headaches. Monitoring IAQ is crucial for ensuring the well-being of occupants and preventing health issues and reduced productivity. Compliance with IAQ regulations is necessary to avoid legal concerns and penalties. The study aims to evaluates IAQ in accordance with the Department of Occupational Safety and Health (DOSH) Malaysia’s Industry Code of Practice on Indoor Air Quality (ICOP 2010), which provides guidelines and acceptable limits for physical and chemical contaminants on the impact on occupants’ health and comfort in Bangunan Persekutuan Kemaman, a government office building in Terengganu, Malaysia. Objective and subjective measurements were collected to assess physical parameters, chemical contaminants, and ventilation performance indicators. The data revealed that the airflow, relative humidity, and light intensity in the building did not meet the ICOP 2010 standards, indicating the need for repair and maintenance of the mechanical ventilation and air-conditioning (MVAC) system. The subjective survey completed by occupants indicated symptoms such as drowsiness, fatigue, and headaches, which are associated with poor IAQ. The study concludes that improvements are necessary to ensure compliance with IAQ regulations and recommends further research on the relationship between air temperature, relative humidity, and older building designs.